2022
DOI: 10.3390/cancers14215218
|View full text |Cite
|
Sign up to set email alerts
|

FTO Inhibits Epithelial Ovarian Cancer Progression by Destabilising SNAI1 mRNA through IGF2BP2

Abstract: Fat mass and obesity-associated protein (FTO) regulates critical pathways in various diseases, including malignant tumours. However, the functional link between FTO and its target genes in epithelial ovarian cancer (EOC) development remains to be elucidated. In this study, the biological functions of FTO were verified in vitro and in vivo. The m6A modification and the binding sites of SNAI1 mRNA were confirmed by m6A RNA immunoprecipitation (MeRIP) and RIP experiments. The actinomycin D assay was used to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…In contrast to the tumour-promoting effects of FTO reported in other studies, a study on ovarian cancer confirmed that FTO expression was suppressed in ovarian cancer and that the demethylation activity of FTO could inhibit the stemness characteristics and self-renewal of ovarian tumour stem cells by regulating the cAMP pathway [134]. Similar to the findings of this study, another study confirmed that low FTO expression was associated with higher FIGO staging in ovarian cancer patients and that FTO decreased the m 6 A level and stability of SNAI1 mRNA, leading to downregulation of SNAI1 expression and inhibition of the epithelial-mesenchymal transition [135].…”
Section: Primary Ovarian Insufficiency (Poi)supporting
confidence: 88%
“…In contrast to the tumour-promoting effects of FTO reported in other studies, a study on ovarian cancer confirmed that FTO expression was suppressed in ovarian cancer and that the demethylation activity of FTO could inhibit the stemness characteristics and self-renewal of ovarian tumour stem cells by regulating the cAMP pathway [134]. Similar to the findings of this study, another study confirmed that low FTO expression was associated with higher FIGO staging in ovarian cancer patients and that FTO decreased the m 6 A level and stability of SNAI1 mRNA, leading to downregulation of SNAI1 expression and inhibition of the epithelial-mesenchymal transition [135].…”
Section: Primary Ovarian Insufficiency (Poi)supporting
confidence: 88%
“…FTO is downregulated in ovarian cancer stem cells and tumours 91 . Downregulation of FTO increases the m6A level in the SNAI1 transcript, enhancing its stability via an IGF2BPs‐dependent manner and promoting epithelial‐to‐mesenchymal transition 92 . FTO inhibits ovarian cancer stem cell self‐renewal by upregulating PDE1C and PDE4B, which subsequently block the cAMP signalling pathway 91 .…”
Section: The Complex Role Of M6a Regulators As Oncoproteins and Tumou...mentioning
confidence: 99%
“…m6A demethylases removes the m6A methylation group of RNA. FTO is involved in processing of micro RNAs (miRNAs) [ 50 ], as well as RNA stability [ 51 ] and metabolism [ 52 ]. ALKBH5 reduces m6A levels and is involved in mRNA export and RA metabolism [ 53 ].…”
Section: Regulators Of Rna Methylationmentioning
confidence: 99%